Catalyzing Collaboration: Reacting to Change Through Collaborative Teacher Professional Development for Transformative Science Education in Nigeria - Usman Rufai Fakai; Aliyu Sa’adu; Muhammad Abdullahi Argungu; Abubakar Sahabi Aliyu (International Journal of Educational and Life Sciences, 2024)
This study investigates the impact of collaborative professional development (CPD) on science education in Nigeria, utilizing a mixed-methods research design. Through a combination of qualitative interviews, focus groups, and classroom observations, alongside quantitative surveys and academic performance data, the study explores how CPD influences teaching practices and student outcomes. Quantitative data showed a statistically significant improvement in student science test scores post-CPD implementation. However, challenges such as resource constraints, time limitations, and insufficient administrative support were identified as barriers to effective CPD implementation. The study highlights the importance of fostering a collaborative culture in schools, providing adequate resources, and ensuring continuous professional growth through structured and supportive policies. These findings underscore the need for educational policymakers to prioritize CPD, integrating it into teacher evaluation and career progression frameworks to achieve sustainable improvements in science education.